SliceSphere: Agile Service Orchestration and Management Framework for Cloud-Native Application Slices - Habibi, Pooyan; Leon-Garcia, Alberto (IEEE access, 2024)
We introduce SliceSphere a comprehensive framework to ease the deployment and management of scalable cloud-native application slices. Slicesphere integrates a strong slicing framework with containerized orchestration engines. We present cloud-native application slicing as an architectural framework that integrates application segmentation, platform abstraction, and cloud-native methodologies into a system known as SliceSphere. This approach forms a cohesive, distributed application environment that surpasses traditional infrastructure limits, allowing organizations to deploy, manage, and scale applications across various computing landscapes with flexibility, scalability, and efficiency. In SliceSphere, each slice, termed SliceKube, operates as an independent unit, encompassing specific features and interacting via well-defined APIs. We have incorporated fundamental microservice design principles and offer extensive service integration, covering everything from specialized multi-stack control planes to essential resources such as computing power, storage, and networking. SliceSphere is built to be flexible, ensuring compatibility regardless of the orchestration engine or infrastructure provider in use. It simplifies complex deployments while enabling users to customize the design of control plane and platform service functionalities to their needs. Additionally, SliceSphere includes two marketplaces that offer pre-configured service-oriented applications and multi-cloud shared resources. A practical demonstration of SliceSphere, designed as a Kubernetes plugin and utilizing open-source technologies, has been developed on the multi-tiered SAVI infrastructure, leveraging a variety of resources. We examine this specific use case, SAVI 2.0, in detail to showcase SliceSphere's ability to address the needs of distributed cloud-native applications across multi-tier and multi-cloud infrastructure.